Enforcing accounts receivable through public auctions - Kinkor, Jiří (2013)
This Bachelor's thesis focuses on the legal ways of enforcing accounts receivable in public auctions within the Czech law. An important part of the thesis is dedicated to a description of accounts receivable formation process and the ways of debt securing. The crucial part refers to the legal framework identification and comparison of the receivables enforcement under obcansky soudni rad and zakon o verejenych drazbach. The entire process of the public auction from the auction proposal to the ownership transfer is described in detail. At last but not least, the possibilities of auction avoidance are mentioned and a brief auction profitability analysis is presented.